Understanding the Influence of Journalists and Politicians on Content: A Cross-Longitudinal Analysis of Chilean Political News Coverage - Mellado-Ruiz, C (SAGE Publications Ltd, 2014)
By means of a cross-longitudinal quantitative content analysis of the Chilean national press, this article analyses the changes in reporting styles and the framing of politics in news coverage between 2006 and 2011, exploring whether the features of political reporting found in studies of Western countries are evident in the case of Chile. According to the data, while politicians trigger the majority of political news stories, political coverage originates significantly more from events than from statements or issues. Likewise, although framing politics as a game is a dominant and significant characteristic of the Chilean press, there is a systematic increase in the public policy frame. The results also indicate low levels of interventionism in covering political news, showing the practice of journalism where politicians have a strong influence on news content. The research allows for discussion on how politicians are adapting to the needs of the media and presents a deeper understanding of the characteristics that define political journalism in new democracies. © The Author(s) 2014.